2022
DOI: 10.1186/s40824-021-00247-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro response of THP-1 derived macrophages to antimicrobially effective PHMB-coated Ti6Al4V alloy implant material with and without contamination with S. epidermidis and P. aeruginosa

Abstract: Aim Periprosthetic joint infections are a devastating complication after arthroplasty, leading to rejection of the prosthesis. The prevention of septic loosening may be possible by an antimicrobial coating of the implant surface. Poly (hexamethylene) biguanide hydrochloride [PHMB] seems to be a suitable antiseptic agent for this purpose since previous studies revealed a low cytotoxicity and a long-lasting microbicidal effect of Ti6Al4V alloy coated with PHMB. To preclude an excessive activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 71 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…In the case of the im-bac models ( Figure 4F ), the co-culture time did not exceed 72 h. For simultaneous seeding, the time varied between 1.5 and 24 h, while for bacteria-first seeding, the range extended from 1 to 72 h. In the case of the cell-first models, the primary culture duration spanned from 0.5 to 4 h. The shorter co-culture times in the cell-first studies can be explained by the focus of those studies on the immediate immunomodulatory effect of the biomaterial upon seeding. However, in the study by Zwicker and co-workers ( Zwicker et al, 2022 ), the co-culture time was extended to 72 h to observe a polarization shift in the macrophages. No such shift was, however, observed in the co-culture while it did occur in their monoculture experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the im-bac models ( Figure 4F ), the co-culture time did not exceed 72 h. For simultaneous seeding, the time varied between 1.5 and 24 h, while for bacteria-first seeding, the range extended from 1 to 72 h. In the case of the cell-first models, the primary culture duration spanned from 0.5 to 4 h. The shorter co-culture times in the cell-first studies can be explained by the focus of those studies on the immediate immunomodulatory effect of the biomaterial upon seeding. However, in the study by Zwicker and co-workers ( Zwicker et al, 2022 ), the co-culture time was extended to 72 h to observe a polarization shift in the macrophages. No such shift was, however, observed in the co-culture while it did occur in their monoculture experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Only one im-bac study has directly focused on macrophage polarization to limit the foreign body response toward a contact-killing surface instead of focusing on enhanced phagocytosis ( Zwicker et al, 2022 ). The monoculture of THP-1 stimulated macrophages on Ti6Al4V, with and without Poly (hexamethylene) biguanide hydrochloride (PHMB) coating, showed that the layer did not induce a pro-inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…S. epidermidis has been shown to induce high levels of pro-inflammatory cytokines secretion, both in vitro and in vivo . Namely, a marked increase in IL-6, IL-8 and TNF-α secretion was detected upon in vitro stimulation of THP-1-derived macrophages [43, 44] and human peripheral blood mononuclear cells [33, 45] with different S. epidermidis strains. Our research team has also shown this pro-inflammatory profile in vivo , in a murine model of bloodstream infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…The cells were cultured in a humidified environment with 5% CO 2 at 37 °C. [ 14 ] To induce macrophage differentiation, they were incubated with PMA (50 ng mL −1 ) for 3 h, washed with phosphate‐buffered saline (PBS) for three times. Then, they were treated with LPS (2 µg mL −1 ) in the absence or presence of Gal for 3 h, then stimulated with ATP (5 mM) for 1 h.…”
Section: Methodsmentioning
confidence: 99%